Incidence and Control of White Grubs in Poplar Nurseries at Nauni in Himachal Pradesh - Sharma, Ajay (Indian Forester, 2004)
Poplars are highly preferred and profitable agro-forestry trees propagated by planting entire transplants raised in nurseries. The plants in the nursery suffer damage by White grubs which feed on its roots. In the experiment conducted to control the pest by using Phorate l0G and Chlorpyriphos in different concentrations , by administering them in two instalments , one at the time of planting and cuttings , and the other 2 months after that , it was found that Phorate l0G @ 20g/m2 was more effective in controlling the pest , although Chlorpyriphos @ 2ml/lt and other concentrations were almost equally good , and resulted in better growth parameters i.e. height and collar diameter.